IMPLEMENTATION OF THE METHADONE MAINTENANCE THERAPY PROGRAM FOR HIGHRISK DRUG PRISONERS - Zakaria, Moch Subhan (Walisongo Law Review (Walrev), 2020)
The harm reduction program is a program that aims to assist inmates who use syringes (IDU's) in overcoming dependence on narcotics medically and to prevent the adverse effects caused by narcotics abuse. Where in general the use of heroin is done by injecting using a syringe alternately, or known as "For Wet" This can cause a new problem that is greater that the outbreak of the HIV/AIDS virus. Most prisoners use injecting narcotics before entering prison and have been infected with the HIV virus, so the risk of transmitting HIV/AIDS to other prisoners is very high. The tendency of the number of relapses (reuse) by prisoners who are in the period of coaching is quite high despite the efforts of strict supervision in the security sector, but in fact in several prisons/detention there is narcotics smuggling in various modes. For this reason, the Indonesian Ministry of Law and Human Rights through the Directorate General of Corrections organizes the P4GN program (Prevention of Eradication of Narcotics Abuse and Circulation) in prisons and detention environments by promoting the principle of "Total Abstinence" meaning that no use of any type of narcotics during coaching in prisons and prisons. But for the type of metadone, which is a type II narcotics can be tolerated because it is used for the purpose of treatment/healing of narcotics dependence and is also a government program implemented by the Ministry of Health as the leading sector.